Leading proton production in deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
The semi-inclusive reaction e+p→e+Xp was studied with the ZEUS detector at HERA with an integrated luminosity of 12.8 pb -1. The final-state proton, which was detected with the ZEUS leading proton spectrometer, carried a large fraction of the incoming proton energy, xL > 0.32, and its transverse momentum squared satisfied p 2T < 0.5GeV2; the exchanged photon virtuality, Q2, was greater than 3GeV2 and the range of the masses of the photon-proton system was 45 < W < 225GeV. The leading proton production cross section and rates are presented as a function of xL, p2 T , Q2 and the Bjorken scaling variable, x. © SISSA 2009.